2010
DOI: 10.1111/j.1748-3743.2009.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Personal and social determinants of health services utilization by Mexican older people

Abstract: Predisposing, enabling and need factors are strong predictors of health services utilization among Mexican older persons. In addition, gender differences exist among this population in relation to health status, but not to health services demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…21,22 However, with advancing age, gender differences in the demand for health services decrease due to the emergence of chronic diseases in both genders, thereby increasing vulnerability. 23 Corroborating the results of this study, some studies has shown that, regarding physical activities, one of the more important fall prevention practices, the proportion of older adult men who perform this is greater than that of older adult women. 24,25 During the aging process women tend to reduce the practice of physical activities that promote muscle growth.…”
Section: Discussionsupporting
confidence: 68%
“…21,22 However, with advancing age, gender differences in the demand for health services decrease due to the emergence of chronic diseases in both genders, thereby increasing vulnerability. 23 Corroborating the results of this study, some studies has shown that, regarding physical activities, one of the more important fall prevention practices, the proportion of older adult men who perform this is greater than that of older adult women. 24,25 During the aging process women tend to reduce the practice of physical activities that promote muscle growth.…”
Section: Discussionsupporting
confidence: 68%
“…Subsequently, all countries need to be prepared to address the consequences of the demographic trends associated with aging populations. Worldwide, the increasing health care demand of older persons requires a better understanding of factors influencing health care service utilization patterns [3]. In several parts of the developing world, primary health care (PHC) use is inadequately understood [4].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors found a negative association between health and healthcare utilization [72,73,74,75,76,77]. These discrepancies may be related to health-status measurements and disability-related conditions among samples.…”
Section: Discussionmentioning
confidence: 89%